Possible use of sucrose for pretreatment and subsequent cryopreservation of newborn rats’ brain-derived neural cells - Vsevolodska, Svitlana; Ochenashko, Olga; Maiorova, Olga; Sukaсh Oleksandr (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):240